A NEURO-LINGUISTIC EXPLORATION OF MIRRORING IN TALK SHOW “THE TONIGHT SHOW STARRING JIMMY FALLON” - Sihombing, Putri Syah Nadillah; Rita Hartati (Bajang Institute, 2024)
Mirroring is a behaviour in which one person unconsciously imitates the gestures, facial expressions, speech or posture of another person. This study aims to analyse how is the NLP mirroring pattern realized and used in the interaction between the host and the guests on “The Tonight Show Starring Jimmy Fallon”. This study uses a qualitative content analysis approach using the theory of NLP mirroring by John Grinder and Richard Bandler (2008) including behavioural mirroring, symbolical mirroring and exchanged matches. This study shows that there are 37 data found. There are 10 (27%) data as behavioural mirroring, 19 (51%) data as symbolical mirroring, and 8 (22%) data as exchanged matches Mirroring is a powerful tool in human interactions that subconsciously shapes how individuals connect with others. By imitating body language, facial expressions, and speech patterns, it creates trust, comfort, and empathy. This can be particularly helpful in vulnerable or stressed situations, leading to smoother communication and stronger relationships. It is hoped that the result of this research is useful for everyone who wants to study about NLP mirroring techniques.